A New Consistency Test for ΛCDM Cosmology Using Galaxy Surveys. (1st June 2022) - Zheng, Jinglan; Zhao, Gong-Bo; Wang, Yuting; Mu, Xiaoyong; Zhao, Ruiyang; Zhang, Weibing; Yuan, Shuo; Bacon, David; Koyama, Kazuya
Abstract: We propose a new consistency test for the ΛCDM cosmology using baryonic acoustic oscillations (BAO) and redshift space distortion (RSD) measurements from galaxy redshift surveys. Specifically, we determine the peak position of f σ 8 ( z ) in redshift z offered by an RSD measurement, and compare it to the one predicted by the BAO observables assuming a flat ΛCDM cosmology. We demonstrate this new test using the simulated data for the DESI galaxy survey, and argue that this test complements those using the background observables alone, and is less subject to systematics in the RSD analysis, compared to traditional methods using values of f σ 8 ( z ) directly.